Relationship of Environmental Condition, Container and Behavior with the Existence of Aedes aegypti Mosquito Larvae in an Endemic Area of Dengue Hemorrhagic Fever, Makassar - Rasjid, Ashari; Yudhastuti, Ririh; Notobroto, Hari Basuki (Pakistan Journal of Nutrition, 2016)
In Rappocini District, Makassar City, dengue hemorrhagic fever (DHF) is an endemic area. The high incidence of dengue is closely related to the population of Aedes aegypti mosquitoes. This study aimed to analyze the relationship between environmental conditions, container and behavior on the existence of the mosquito of Aedes aegypti. This was an observational study with a cross-sectional study design. The sample size was 100 houses and they were selected via simple random sampling. In depth interviews, measurements and observations were conducted to achieve the research objective. Data were analyzed by Chi-square and Fisher's exact tests to determine the relationship of environmental conditions (temperature, humidity), container (container type) and the characteristics of residents(knowledge, attitude and actions) with the presence of Aedes aegypti larvae. This study found a significant relationship between humidity (p = 0.000), type of container (p = 0.004), knowledge (p = 0.001) and practice (p = 0.001) in the presence of Aedes aegypti mosquito larvae. Meanwhile, the air temperature and the attitude of the respondents were not significantly related with the results of the study of Aedes aegypti larvae. In conclusion, the environmental conditions, container and community characteristics in Rappocini District, Makassar City are not conducive to mosquito nest cleaning (PSN); thus, the density of Aedes aegypti is high in this region. The density of larvae showed high dispersion, i.e., HI = 68%, CI = 30.6%, BI = 82% and DF = 8. Public participation in the eradication of dengue disease via eradication of the mosquito Aedes aegypti is recommended and would involve cleaning the environment, especially by draining water stores, which are nests for mosquito larvae.